Bitcoin in Islamic Jurisprudence: Between Innovation and Speculation - Jundullah Rifqi Prasmanto; Anang Ma’ruf; Muhammad Fathurrahman Assidiq; Muhammad Faiz Diyaulhaq (Journal of Islamic Law and Legal Studies, 2025)
This study examines the status of Bitcoin and its underlying blockchain technology from the perspective of Islamic law. The research utilizes a qualitative library-based method, analyzing primary sources of Islamic jurisprudence alongside recent academic studies. It explores key Shariah principles such as mal mutaqawwam, maysir, gharar, and riba, in assessing Bitcoin's permissibility. The findings reveal that while Bitcoin's volatility, speculation, and lack of intrinsic value raise concerns under Islamic finance, the asset does not inherently involve interest (riba). Furthermore, the research distinguishes between the controversial nature of Bitcoin and the positive potential of blockchain technology, which aligns with the objectives of maqasid al-shariah, particularly in promoting transparency, financial inclusion, and ethical conduct. The study concludes that while Bitcoin may remain contentious, blockchain offers significant opportunities for Shariah-compliant financial innovation when supported by appropriate regulation and ethical oversight.